Zeitschrift für Evangelische Ethik : Kommentare, Studien, Berichte, Dokumentationen, Diskussionen, Rezensionen, Bibliographie (Gütersloher Verlagshaus, 1957)
Zeitschrift für Evangelische Ethik ... ... first published in 1957, the Zeitschrift für Evangelische Ethik provides a forum for expert discussions within the field of protestant ethics. Within the German-speaking countries, it is the leading journal in this realm and beyond that has found numenous readers especially in Scandinavia and the Anglo-American world. ... covers a wide spectrum of topicsTopics range from fundamental challenges in theological and philosophical ethics to very specific questions of applied ethics, e.g. discussions about a fair economic system or debates on medical ethics or bioethics, natural and environmental ethics, culture, diversity of cohabitation, etc. Dedicated to current topics, this journal also presents studies on the history of Protestant ethics and seeks dialogue with cognate theological disciplines. ... fosters discourseEthics is a discursive process. It is performed by the exchange of arguments and interaction of diverse social and (cross-)disciplinary perspectives. This journal does not aim at a monologue of academic theology, nor at profiling certain theological trend. Rather, everyone working on ethical problems from a Protestant perspective is dependent on expert knowledge from various areas. This is why not only theologians, but also scholars and and practitioners from diverse professional backgrounds publish in ZEE: lawyers, physicians, scientists, sociologists, economists, politicians, managers, unionists, and others. Through a variety of positions presented, this journal aims at encouraging discussions also within protestant ethics. ...is published quarterlyEach issue presents 80 pages of commentaries, in-depth analyses on spec